2015
DOI: 10.1007/s40495-014-0002-x
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Regulation by Sulforaphane: Opportunities for Breast and Prostate Cancer Chemoprevention

Abstract: Sulforaphane (SFN) is a phytochemical derived from cruciferous vegetables that has multiple molecular targets and anti-cancer properties. Researchers have demonstrated several chemopreventive benefits of SFN consumption, such as reductions in tumor growth, increases in cancer cell apoptosis, and disruption of signaling within tumor microenvironments both in vitro and in vivo. Emerging evidence indicates that SFN exerts several of its chemopreventive effects by altering epigenetic mechanisms. This review summar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 98 publications
0
34
0
4
Order By: Relevance
“…Here our observed outcome is inhibition of bladder cancer cell growth by broccoli ITCs, and we see this outcome associated with epigenetic modulations, including acetylation changes of histone H3 and hypo-phosphorylation of histone H1. Future studies will focus on the persistence of the effect of the epigenetic modification and cell viability [32, 48, 49]. …”
Section: Discussionmentioning
confidence: 99%
“…Here our observed outcome is inhibition of bladder cancer cell growth by broccoli ITCs, and we see this outcome associated with epigenetic modulations, including acetylation changes of histone H3 and hypo-phosphorylation of histone H1. Future studies will focus on the persistence of the effect of the epigenetic modification and cell viability [32, 48, 49]. …”
Section: Discussionmentioning
confidence: 99%
“…In a previous report, SFN was shown to prevent the QA‐induced neurotoxicity as a result of the activation of Nrf2/ARE pathway . Thus, SFN activates the expression of a large range of cytoprotective genes involved in cellular survival and endogenous defense . However, this study was conducted using whole striatal tissue homogenates, and it did not distinguish between cytosolic and mitochondrial effect.…”
Section: Introductionmentioning
confidence: 92%
“…Previous studies have indicated that SFN has many biological properties, including anti-oxidant, anti-inflammatory, and anti-bacterial effects [11,12]. SFN has been found to act as a tumor suppressor in many different cancers during cancer progression, including oral, breast, liver, colon, and prostate cancers [13][14][15][16]. In addition, it has been demonstrated that SFN has the ability to prevent carcinogen-induced initiation of oral cancer [14].…”
Section: Introductionmentioning
confidence: 99%